Long-term heavy metal accumulation in sediment dust of schools in Vilnius: a case study - Unsal, Murat Huseyin; Ignatavičius, Gytautas; Valskienė, Roberta; Valskys, Vaidotas (International Conference “Environmental Engineering”, 2023)
This study aims to determine concentrations of chromium (Cr), lead (Pb), zinc (Zn), arsenic (As), mercury (Hg), and copper (Cu) their contamination characteristics, in the samples of dust collected from eleven different schools in the Vilnius region and were investigated. X-ray fluorescence spectrometry was used to analyze the collected dust samples. The geo-accumulation index (Igeo) and pollution load index were used to determine the contamination level (PLI). The average concentrations distributed as follows: Zn > Cr > Cu > Pb > As > Hg. Ni and Cd were below the detection threshold. Average Igeo values of schools’ show that above 3 class observed. Only in three schools that Hg was detected and for these schools Igeo values shows no contamination according to index classes. The levels of Cu, Zn in all schools exceeded the contamination limit of Igeo value class 6, and the levels of Pb, Cr in some schools also exceeded this limit. As for PLI values, in all the other schools, were above 1, indicating a decrease in the quality of the site.
Keywords: indoor dust; school dust; heavy metals; PLI; geo-accumulation; Vilnius